Rhadinovirus vector-derived human telomerase reverse transcriptase expression in primary T cells - Toptan, Tuna; Ensser, Armin; Fickenscher, Helmut (Gene therapy, 2010)
The rhadinovirus herpesvirus saimiri (HVS) as a gene delivery vector allows large DNA insertions and long-termed gene expression. In the case of T-cell transduction, such vectors use the viral transformation-associated genes of HVS C488 for T-cell amplification. In this report, we investigated whether the gene for the catalytic telomerase subunit human telomerase reverse transcriptase (hTERT) can substitute for the transformation-associated genes in rhadinoviral T-cell transduction and amplification. By using virus mutants generated by en passant mutagenesis from bacterial artificial chromosomes, we observed a very early and functional transgene expression even by virus mutants without transformation-associated genes. The markers of T-cell transformation by HVS, namely CD2 hyperreactivity, overexpression of interleukin-26, and of the tyrosine kinase Lyn could neither be induced nor enhanced by ectopic hTERT expression. When the viral transformation-associated genes were replaced by the hTERT gene, it was not sufficient for growth transformation, although hTERT was efficiently transduced and functionally expressed by the rhadinovirus vector. Thus, the transformation-associated proteins StpC and Tip are responsible for the T-cell phenotype after transduction by HVS and, additionally, modulate telomerase activity independently of hTERT expression.